2017
DOI: 10.12692/ijb/10.5.319-342
|View full text |Cite
|
Sign up to set email alerts
|

Application of polyamines in horticulture: A review

Abstract: Polyamines are ubiquitous organic compounds in plants that are involved in various physiological functions; they play key role in the regulation of ion channels and molecule transportation in the cell membrane. Being positively charged, polyamines can bind to macromolecules such as DNA, RNA and proteins, hence stabilize them against free radicals activity. Their importance with respect to plant growth and development is already

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 68 publications
(81 reference statements)
1
2
0
1
Order By: Relevance
“…The regeneration responses of PLBs from explants grown on medium containing different concentrations of PAs (Put, Spd, and Spm) were similar to those of the control treatment (without PAs), so this supplementation to MSM/2 medium is not recommended. PAs can improve plant growth and development because of their effects on cell division and differentiation(Abbasi et al 2017) and these results were observed in this study, with high percentages of PLBs regeneration in apical tTCLs (83.33 to 100%). In our study, PAs were tested with protocorms obtained after 120 days of in vitro germination, while in the experiments performed with microalgae and PAs, the protocorms were 90 days old.…”
supporting
confidence: 82%
“…The regeneration responses of PLBs from explants grown on medium containing different concentrations of PAs (Put, Spd, and Spm) were similar to those of the control treatment (without PAs), so this supplementation to MSM/2 medium is not recommended. PAs can improve plant growth and development because of their effects on cell division and differentiation(Abbasi et al 2017) and these results were observed in this study, with high percentages of PLBs regeneration in apical tTCLs (83.33 to 100%). In our study, PAs were tested with protocorms obtained after 120 days of in vitro germination, while in the experiments performed with microalgae and PAs, the protocorms were 90 days old.…”
supporting
confidence: 82%
“…Mahgoub et al (2011) reported that the application of polyamines in cut flower preservative solutions improved flower fresh weight. Abbasi et al (2017) also observed the positive effect of polyamines, such as putrescine, on inhibiting flower aging and prolonging post-harvest life. Mohammadi et al (2014) obtained the highest relative fresh weight from gladiolus flowers treated with 100 mg L −1 putrescine + 100 mg L −1 salicylic acid.…”
Section: Public Interest Statementmentioning
confidence: 85%
“…Means comparison revealed that the application of 150 and 300 ppm of putrescine reduced wilting percentage by 43.45 and 40.11 percent, respectively, but when only 300 ppm of putrescine was applied, no significant differences were entailed versus the control (Figure 7). Abbasi et al (2017) reported the positive effect of polyamines including putrescine on inhibiting flower aging and the extension of post-harvest life. According to the results of ANOVA, vase life was significantly influenced by silver thiosulfate and putrescine at the p < 0.05 and p < 0.01 levels, respectively, but the interactive effect of these factors was not significant for this trait (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Plants sprayed with foliar putrescine have shown an alleviating mechanism against negative drought effects through well-regulated metabolic routes (Chen et al, 2019), the polyamines are plant growth regulators that can increase cellular division and link to the membranes in order to stabilize and protect them against peroxidation (Abbasi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%